2009
DOI: 10.1242/dev.028431
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamidase modulation of NAD+ biosynthesis and nicotinamide levels separately affect reproductive development and cell survival inC. elegans

Abstract: Nicotinamide adenine dinucleotide (NAD+) is a central molecule in cellular metabolism and an obligate co-substrate for NAD+-consuming enzymes, which regulate key biological processes such as longevity and stress responses. Although NAD+ biosynthesis has been intensely studied, little analysis has been done in developmental models. We have uncovered novel developmental roles for a nicotinamidase(PNC), the first enzyme in the NAD+ salvage pathway of invertebrates. Mutations in the Caenorhabditis elegans nicotina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
89
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(95 citation statements)
references
References 44 publications
(60 reference statements)
6
89
0
Order By: Relevance
“…We have revealed that the reproductive system as well as muscle development and function are particularly sensitive to loss of ability to synthesize NAD ϩ via a salvage pathway from nicotinamide and that these phenotypes are caused by the tissue-specific effects of both nicotinamide and nicotinic acid levels (12)(13)(14). In this study we demonstrate that salvage synthesis has a mild global negative effect on NAD ϩ levels but that mitochondrial function is preserved when salvage synthesis from nicotinamide (NAM) 2 is blocked.…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…We have revealed that the reproductive system as well as muscle development and function are particularly sensitive to loss of ability to synthesize NAD ϩ via a salvage pathway from nicotinamide and that these phenotypes are caused by the tissue-specific effects of both nicotinamide and nicotinic acid levels (12)(13)(14). In this study we demonstrate that salvage synthesis has a mild global negative effect on NAD ϩ levels but that mitochondrial function is preserved when salvage synthesis from nicotinamide (NAM) 2 is blocked.…”
mentioning
confidence: 74%
“…Although NAMPT and nicotinamidase are distinct enzymes and co-exist only in select organisms (15), they have biologically comparable functions in consuming NAM and producing NAD ϩ . Human NAMPT can partially compensate for the loss of the C. elegans nicotinamidase pnc-1, demonstrating an equivalent biological role for the two enzymes (12). Finally NAD ϩ is produced from the essential amino acid tryptophan through the kynurenine pathway, which produces quinolinic acid that is converted to nicotinic acid mononucleotide via quinolinic acid phosphoribosyltransferase (21).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent study revealed that the ku212 allele maps to the pnc-1 gene locus, which encodes for a nicotinamidase (van der Horst et al, 2007;Vrablik et al, 2009). Nicotinamidases are the first enzymes of the NAD þ salvage pathway in invertebrates, using nicotinamide (NAM) as a substrate (Magni et al, 1999).…”
Section: Vulva Cell Necrosismentioning
confidence: 99%